Wage Structure and the Incentive Effect of Promotions - Marco van Herpen; Kees Cools; Mirjam van Praag (Tinbergen Institute, 2004)
This paper studies wage structure characteristics and their incentive effects within one firm. Based on personnel records and an employee survey, we provide evidence that wages are attached to jobs and that promotions play a dominant role as a wage determinant. We furthermore show that a promotion affects both intrinsic and extrinsic motivation significantly, though in two different ways: An expected promotion increases extrinsic motivation whereas intrinsic motivation is highest subsequent to a realized promotion. The relationship between extrinsic motivation and expected promotions implies that promotions have a clear incentive effect, consistent with a key – not yet tested – prediction of the tournament model.
Keywords: J41; J33; M51; M52; 330; promotions; incentives; tournament model; internal labor market; extrinsic motivation; intrinsic motivation; Lohnstruktur; Leistungsanreiz; Leistungsentgelt; Leistungsmotivation